STABILITY ANALYSIS FOR RAILWAY TUNNEL XYZ AT STA 359+433 UNTIL STA 359+427 WITH FINITE ELEMENT METHOD - Muhammad Riski Afdol - NIM : 12114024,
Based on the Strategic Plan of the Ministry of Communications in 2015-2019, Railway Development is one of the medium-term priorities that will be conducted in the period 2015-2019 as a means of transportation network in accelerating and expanding economic development in Indonesia. Tunnel XYZ is the first double track railway tunnel in Indonesia located in Central Java. In the excavation and construction using New Austrian Tunneling Method (NATM). Later the tunnel will replace the existing track of single track that already exists. In designing railway tunnels, considering their function is used by many people and its use for a long time, the stability of the tunnel becomes an important thing to note. This study aims to determine the stability of the tunnel using Phase2 software with finite element calculation method The stability analysis of the tunnel was conducted in 5 research sites: STA 359 + 433, STA 359 + 431, STA 359 + 430, STA 359 + 429 and STA 359 + 427. In each research sites, observations were made before and after buffering. From the geotechnical mapping, modeling using Phase2 software was used to find out the strength factor, tunnel displacement and the yielded elements distribution of the material and the buffer used. In addition, the calculation of tunnel displacement values at the ACE point of the monitoring data using the total station will be compared with the value of the displacement from the modeling results. The result of modeling shows that the displacement value at the ACE point approaches the displacement value of the monitoring data so that the modeling is valid. The buffer used works very well in improving tunnel stability. This can be seen with increasing strength factor after buffering, tunnel displacement decreasing after buffering, and the absence of yielded elements in the material on the roof, right, and left of tunnel after installed the buffer so that the tunnel is in stable condition.